A critical appraisal of guidelines used for management of severe acute malnutrition in South Africa's referral system - Faith Nankasa Mambulu-Chikankheni; John Eyles; Ejemai Amaize Eboreime; Prudence Ditlopo (BMC, 2017)
Abstract Background Focusing on healthcare referral processes for children with severe acute malnutrition (SAM) in South Africa, this paper discusses the comprehensiveness of documents (global and national) that guide the country's SAM healthcare. This research is relevant because South African studies on SAM mostly examine the implementation of WHO guidelines in hospitals, making their technical relevance to the country's lower level and referral healthcare system under-explored. Methods To add to both literature and methods for studying SAM healthcare, we critically appraised four child healthcare guidelines (global and national) and conducted complementary expert interviews (n = 5). Combining both methods enabled us to examine the comprehensiveness of the documents as related to guiding SAM healthcare within the country's referral system as well as the credibility (rigour and stakeholder representation) of the guideline documents' development process. Results None of the guidelines appraised covered all steps of SAM referrals; however, each addressed certain steps thoroughly, apart from transit care. Our study also revealed that national documents were mostly modelled after WHO guidelines but were not explicitly adapted to local context. Furthermore, we found most guidelines' formulation processes to be unclear and stakeholder involvement in the process to be minimal. Conclusion In adapting guidelines for management of SAM in South Africa, it is important that local context applicability is taken into consideration. In doing this, wider stakeholder involvement is essential; this is important because factors that affect SAM management go beyond in-hospital care. Community, civil society, medical and administrative involvement during guideline formulation processes will enhance acceptability and adherence to the guidelines.